(untitled) (Baghdad Science Journal, 2021)
A theoretical and protection study was conducted of the corrosion behavior of carbon steel surface with different concentrations of the derivative (Quinolin-2-one), namly (1-Amino-4,7-dimethyl-6-nitro-1H-quinolin-2-one (ADNQ2O)). Theoretically, Density Functional Theory (DFT) of B3LYP/ 6-311++G (2d, 2p) level was used to calculate the optimized geometry, physical properties and chemical inhibition parameters, with the local reactivity to predict both the reactive centers and to locate the possible sites of nucleophilic and electrophilic attacks, in vacuum, and in two solvents (DMSO and H2O), all at the equilibrium geometry. Experimentally, the inhibition efficiencies (%IE) in the saline solution (of 3.5%) NaCl were studied using potentiometric polarization measurements. The results revealed that the (%IE) for carbon steel corrosion by ADNQ2O is (89.88%). The obtained thermodynamic parameters support the physical adsorption mechanism. The adsorption followed the Langmuir isotherm. The surface change on carbon steel was studied using SEM (Scanning Electron Microscopy).